A newly established bovine intestinal epithelial cell line is effective for in vitro screening of potential antiviral immunobiotic microorganisms for cattle - Chiba, Eriko (Res Vet Sci, 2012)
We evaluated whether a bovine intestinal epithelial (BIE) cell line could serve as a useful in vitro model system for studying antiviral immune responses in bovine intestinal epithelial cells (IECs) and for the primary screening of immunobiotic microorganisms with antiviral protective capabilities. Immunofluorescent analyses revealed that toll-like receptor 3 (TLR3) was expressed in BIE cells, and the results of real-time quantitative PCR showed that these cells respond to stimulation with poly(I:C) by up-regulating pro-inflammatory cytokines and type I interferons. In addition, we demonstrated that BIE cells are useful for the primary screening of immunobiotic lactic acid bacteria strains which are able to beneficially modulate antiviral immune responses triggered by TLR3 activation in bovine IECs. The characterization of BIE cells performed in the present study represents an important step towards the establishment of a valuable bovine in vitro system that could be used for the development of immunomodulatory feed for bovine hosts.